"Polokočovníci" / Migrační trajektorie olašských Romů na Prešovsku od poloviny 19. století až do zániku kočování - Hajská, Markéta (Romano džaniben, 2016)
The study focuses on migration trajectories of one community of Vlach Roms which has settled in the second half of the 19th century in eastern Slovakia. Taking a  diachronic perspective, the text presents the migration histories of this group of people since their arrival to the territory of Slovakia until the termination of their itinerancy one hundred years later. The case study is based on data gathered via a combination of social anthropologic and oral history approaches as well as archival research (mainly in parish registers). Using the results of her long term field research the author aims at reconstructing the travelling routes of the community in focus. She pays attention to the process and degree of settlement of this group in the particular municipality in eastern Slovakia, and the subsistence activities of the Roms linked with travelling life, which some of the community members pursued even after their settlement in the village. While doing so she also enters into debate with existing Romani studies literature on the adequacy of labellingthe group „semi-nomadic“ – as has so far been done.